DEVELOPMENT OF STUDENTS' SELF-EFFICACY IN THE PROCESS OF ADAPTATION TRAINING - Muzуka, Olena (Educological discourse, 2020)
The article analyzes the results of theoretical and empirical studies of self-efficacy as a factor of successful professionalization. The experience of the development of adaptive training for first-year students based on the development of self-efficacy is described. The theoretical and organizational foundations of the training are substantiated. The theoretical model of the development of self-efficacy in the process of adaptation training is described. Self-efficacy is seen as a system-forming factor in the adaptation of first-year students and their primary professionalization. The development of self-efficacy in the process of adaptation training is based on the analysis of real life situations, the specific organization of group work and feedback. The result of value interaction in the process of reflection by students of their own and others' experience is the amplification and partial homogenization of group and individual value space, which in turn is a valuable basis for the adaptation of first-year students. The psychological content of training is the process of value interaction. The exchange of valuable experience in the professional sphere leads to the broadening of the ideas of each participant about the possible range of development of professional abilities, and consequently to the increase of the potential of development of the value sphere and professional motivation of each student.